Integration of FinTech Applications in Public Health Strategies for Sustainable Development - Abedalrhman, Kahtan; Alzaydi, Ammar (International Journal of Engineering and Management Research, 2024)
In the era of rapid technological evolution, the convergence of financial technology (FinTech) and public health emerges as a pivotal strategy for advancing sustainable development. This article delineates the multifaceted integration of FinTech applications within public health systems globally, scrutinizing their historical progression, current implementations, and future trajectories. It evaluates the economic viability, technological underpinnings, and socio-environmental impacts of such integrations, drawing on diverse regional case studies to illustrate varying degrees of adoption and success. The discourse extends to an in-depth analysis of the economic ramifications, including a thorough cost-benefit assessment, and explores the broader social implications, particularly in terms of accessibility, inclusivity, and ethical considerations. Additionally, the environmental dimensions of sustainable health practices financed through innovative FinTech solutions are examined. The regulatory landscapes that govern these integrations are critically analyzed, offering a compendium of policy recommendations aimed at optimizing the synergy between FinTech and public health. As the paper forecasts emerging technologies' potential impacts, it identifies persistent challenges and proposes strategic solutions to overcome barriers to integration. The concluding remarks underscore the necessity for global stakeholders to collaborate in fostering an equitable and sustainable future, catalyzed by the strategic alliance of FinTech and public health initiatives. This comprehensive exploration not only highlights the transformative potential of FinTech in public health but also champions a call to action for sustained, integrated development efforts.